please answer the question and how you answered it NO LINKS AND NO WEBSITES
![please answer the question and how you answered it NO LINKS AND NO WEBSITES class=](https://us-static.z-dn.net/files/d28/13a22426e07bf852ab8bfa754e4f3c3e.jpg)
Answer:
y= 27-6x
Step-by-step explanation:
For the first equation you add 6x on both sides which will leave us at
-y=-27+6x. You then divide both sides by a -1 to make the y positive so then it'll give us the equation y= 27-6x . For the second equation subtract 18x on both sides which will leave us with the equation 3y= 81-18x . Divide each side by 3 to get the y by itself. Then the equation will be y=27-6x